PELAKSANAAN PERPANJANGAN ATAU PEMBAHARUAN HAK GUNA BANGUNAN DI ATAS TANAH NEGARA PADA KANTOR PERTANAHAN KABUPATEN WONOGIRI - RAHAYU, BUDI (Dinamika Hukum, 2015)
In the setting of the Renewal and Reform Implementation of Right to Build (HGB) as stipulated in Government Regulation No. 40 of 1996 and PMNA / KBPN No. 9 of 1999 in fact there is a difference in the meaning of both. In this regard an important and interesting to study about how the implementation of extension and renewal of Broking in Land State In Wonogiri District Land Office. The aim is to assess the implementation of the extension and renewal HGB on land by the State Land Office Wonogiri and legal certainty. The approach used in this study is empirical juridical. The data used is primary data sourced from the relevant authorities in the implementation of the provision of extension and renewal HGB in Wonogiri District Land Office, as well as secondary data obtained from the materials related laws and relevant. In general, based on interviews with the competent authorities in the process of granting the extension and renewal of HGB Land Office Wonogiri and is reinforced by the evidence of the application for the extension and renewal of the HGB shows that the expiration date of the HGB, date of registration and the publication of the decree are in a grace 2 years. Related to the research results it can be concluded that the implementation of the extension and renewal of HGB at Wonogiri District Land Office to comply PMNA / Ka.BPN No. 9 of 1999. The guarantee legal certainty in the conduct of the extension and renewal can not be separated from the argument HGB officials also consider the decision maker public service. Keywords: Building rights, the State Land